Peran Pendidikan Agama Kristen Terhadap Remaja dalam Mencegah Perilaku Konsumerisme di Era Digital - Kevin Samuel Kamagi (Jurnal Shanan, 2022)
This research is based on the occurrence of a change in people's consumption. which was originally carried out on goods and services that contain use value has now change to consumption of goods and services that are carried out for the satisfaction of desires or what is called consumerism. The digital era is an era of good development for society. but, the digital era also has a negative impact on public consumption. because of the acceleration of more practical information, people are easily to consumptive and trapped with consumerism. Teenagers are groups that need to be guided, because the Teenagers phase still wants recognition of their identity in their lives so that acting consumptively can be an option for recognizing identity. The purpose of this study is to provide a description of how Christian Religious Education exists to provide understanding to teenager in preventing consumerism in the digital era. The research method used is qualitative, with the collection of library study data. The results is indicate that Christian religious education can teach about how teenagers should not be trapped by worldly things, prioritize use values in life, and how teenagers can become self-absorbed individuals. In this education, the competence of educators who are not hedonic is needed and in the evaluation of learning, the congruence evaluation model can be used.